A Review Discussing Synthesis and Translational Studies of Medicinal Agents Targeting Sphingolipid Pathways - Sameena Mateen; Jordan Oman; Soha Haniyyah; Kavita Sharma; Ali Aghazadeh-Habashi; Srinath Pashikanti (Biomolecules)
Sphingolipids (SLs) are a class of bioactive lipids characterized by sphingoid bases (SBs) as their backbone structure. These molecules exhibit distinct cellular functions, including cell growth, apoptosis, senescence, migration, and inflammatory responses, by interacting with esterases, amidases, kinases, phosphatases, and membrane receptors. These interactions result in a highly interconnected network of enzymes and pathways, known as the sphingolipidome. Dysregulation within this network is implicated in the onset and progression of cardiovascular diseases, metabolic disorders, neurodegenerative disorders, autoimmune diseases, and various cancers. This review highlights the pharmacologically significant sphingoid-based medicinal agents in preclinical and clinical studies. These include myriocin, fingolimod, fenretinide, safingol, spisulosine (ES-285), jaspine B, D-e-MAPP, B13, and α-galactosylceramide. It covers enantioselective syntheses, drug development efforts, and advances in molecular modeling to facilitate an understanding of the binding interactions of these compounds with their biological targets. This review provides a comprehensive evaluation of chiral pool synthetic strategies, translational studies, and the pharmacological relevance of sphingolipid-based drug candidates, offering a pathway for future research in sphingolipid-based therapeutic development.